Transformation of Paddy Field Use in Intermountain-Type Basins Using Evidence from the Structure and Function Perspective of Karst Mountain Areas in Southwest China - Mei Chen; Yangbing Li; Fang Tang; Qian Xu; Meng Yu; Han Zhang; Xue Li (Agronomy, 2023)
China’s southwestern karst area exhibits many mountains and little flat lands, and intermountain basins (IBs) (locally named “bazi”) are one of their typical landform types. Comparative studies on land use in the core of typical landforms in karst mountain areas are relatively lacking. Studying the evolution and transformation patterns of intermountain basin paddy fields use (IBPFU) to optimize land resources in mountainous areas is important. Based on structural and functional perspectives, this study established a research framework on the evolution and transformation of IBPFU in karst mountainous areas, and analyzed the evolution and transformation patterns of IBPFU in Guizhou Province from 1966 to 2020 by measuring land use change and applying the moving window method and morphological spatial pattern analysis (MSPA) model. The study showed that the evolution of IBPFU is characterized by reversibility and irreversibility, diversity, and stages. The transition of IBPFU requires a trade-off among regional socioeconomic development, ecological protection, and food security. The commonality of land use transitions in IB and sloped land (SL) is reflected in the diversity of their land use functions. This study provides a reference for a comprehensive understanding of land use transitions and sustainable development in the mountainous karst regions of southwest China by providing in-depth examinations of the land use transition of IB, which is different from SL, via the long time series evolution of core land use types. The research framework and research method constructed here also apply to other regions.